Implementation of Internet of Things (IoT) in a Plastic Blow Moulding Machine and Its Performance Measurement - Faqih, Muhammad Fadhlurrohman; Darsin, Mahros; iMuttaqin, Aris Zainul; Yudistiro, Danang (Journal of Mechanical Engineering Science and Technology (JMEST), 2021)
Efficiency and effectiveness are indispensable things in the production process. Accurate use of existing resources and the shorter cycle time of production are of particular concern to optimize the production process. This research aims to implement automation to a conventional blow molding. An advanced attempt was carried out to use the Internet of Things (IoT) to increase its efficiency while maintaining the quality of the products. The use of the nodeMCU microcontroller and the blynk application allows the operator to operate the machine without having to come into or having direct contact with the machine. The performance of automation and IoT were tested by examining the products using Taguchi design using quality criteria of nominal the best. The efficiency of the system was also considered by comparing the cycle production time. S/N ratio of Taguchi analysis showed that the optimum volume of the bottle would be achieved when applying the temperature, injection time, and holding time of 190 oC, 14 minutes, and 5 minutes respectively. The error or deviation is only 0.41%. The application of the IoT system takes 34.45 seconds for a cycle time production, which is 3.76 seconds faster than a conventional system.